The Impact Of Elementary School Teachers’ Capabilities In Managing The Classroom On Students Disobey The Rules Of Discipline - Liu Han; Dhakir Abbas Ali; AMIYA BHAUMIK (Revista Electronica de Veterinaria, 2024)
A sizeable portion of the disruptions that take place in educational institutions may be traced back to teachers who do not adequately enforce the rules and regulations that are in place within the environment of the classroom. For the purposes of this study, the major focus is on the disciplinary measures that are performed by students when they are attending elementary school. In order to analyse the connection between successful classroom management practices and the findings that were described above, the goal of this research is to investigate the correlation. In order to accomplish the objective of collecting data for the research, interviews were carried out with around 620 teachers from chines. In order to ascertain the level of significance that the regression coefficient has, a study into the statistical significance of the coefficient was carried out. It was discovered that the administrative skills of teachers had a significant relationship with the extent to which pupils followed the rules and regulations that were in place. According to the findings, there was a positive correlation between the overall disciplinary behaviour of students and the first, second, third, fourth, and sixth dimensions of classroom management those instructors had. On the other hand, there was a negative correlation with the fifth dimension that teachers used within their classroom management strategies. Research has shown that there is a significant association between the ability of students to act in a disciplined way in the classroom and important teacher attributes that are associated to classroom management. This correlation has been proved to be significant.